Late Barremian / Early Aptian Re–Os age of the Ipubi Formation black shales: Stratigraphic and paleoenvironmental implications for Araripe Basin, northeastern Brazil. (October 2020) - Lúcio, Thales; Souza Neto, João Adauto; Selby, David
Abstract: The Ipubi Formation of the Santana Group, Araripe Basin, Brazil, is characterized by black shales and overlying evaporite deposits and is suggested to record the transition from lacustrine to marine depositional environments. To date, the age of the black shales, constrained only by microfossils, is poorly determined, with ages spanning 25 myrs from 125 to 100.5 Ma (Aptian-Albian). Here we present new Re–Os elemental and isotopic data to provide the first absolute age for those rocks of the Ipubi Formation and an improved understanding of the depositional paleoenvironment of the Araripe Basin. The Re–Os isotope data for Ipubi Formation black shales yields a depositional age of 123 ± 3.5 Ma, with a highly radiogenic initial 187 Os/ 188 Os composition (Osi ) of 1.97 ± 0.02. The Re–Os age indicates that the deposition of the Ipubi Formation black shales occurred during the Late Barremian/Early Aptian, prior to the onset of OAE 1a, in a highly restricted marine/lacustrine setting. Highlights: The Highlights considered for the manuscript are: 1. The first Re–Os absolute age (123 ± 3.5 Ma) for Ipubi Formation black shales in the Araripe Basin indicates the formation is Late Barremian/Early Aptian and not Aptian/Albian, and was deposited prior to the onset of OAE1a. 2. Based on the Re–Os age a new chronostratigraphic model is proposed for the Santana Group, Araripe Basin. 3. Highly radiogenic 187 Os/ 188 Os compositions of 1.97 ± 0.02 imply that the Araripe Basin records a highly restricted water mass during the Late Barremian/Early Aptian.